p-Type Two-Dimensional Semiconductors: From Materials Preparation to Electronic Applications - Tang, Lei; Zou, Jingyun (Nano-Micro Letters, 2023)
Two-dimensional (2D) materials are regarded as promising candidates in many applications, including electronics and optoelectronics, because of their superior properties, including atomic-level thickness, tunable bandgaps, large specific surface area, and high carrier mobility. In order to bring 2D materials from the laboratory to industrialized applications, materials preparation is the first prerequisite. Compared to the n-type analogs, the family of p-type 2D semiconductors is relatively small, which limits the broad integration of 2D semiconductors in practical applications such as complementary logic circuits. So far, many efforts have been made in the preparation of p-type 2D semiconductors. In this review, we overview recent progresses achieved in the preparation of p-type 2D semiconductors and highlight some promising methods to realize their controllable preparation by following both the top–down and bottom–up strategies. Then, we summarize some significant application of p-type 2D semiconductors in electronic and optoelectronic devices and their superiorities. In end, we conclude the challenges existed in this field and propose the potential opportunities in aspects from the discovery of novel p-type 2D semiconductors, their controlled mass preparation, compatible engineering with silicon production line, high-κ dielectric materials, to integration and applications of p-type 2D semiconductors and their heterostructures in electronic and optoelectronic devices. Overall, we believe that this review will guide the design of preparation systems to fulfill the controllable growth of p-type 2D semiconductors with high quality and thus lay the foundations for their potential application in electronics and optoelectronics. Highlights: 1 Compared to the n-type two-dimensional (2D) semiconductors, the family of p-type 2D semiconductors is relatively small, which limits the broad integration of 2D semiconductors in potential applications. Here, the discovery and preparation of p-type 2D semiconductors are very important and meaningful. 2 This review presents a timely and in-depth overview on the preparation and applications of p-type 2D semiconductors, which would help the related researchers to grasp the dynamics of this field and thus lay the foundations for their potential application in electronics and optoelectronics.